Bali Houses : New Wave Asian Architecture and Design - Francione, Gianni (Tuttle Publishing, 2012)
Bali Houses is a beautiful introduction to the contemporary Asian design movement known as ""Bali Style."" With visually stunning photographs, architect Gianni Francione shows how Balinese designers are updating the traditional aesthetic principles to create a new international flavor. Villas showcasing the characteristic open, panoramic style are now being made with marble and stone. Architects are applying modern techniques to resort bungalows made of customary coconut wood. The author shows how these departures from tradition are influencing everything from interior design to textiles, tabl.